Causal Diagrams for Treatment Effect Estimation with Application to Efficient Covariate Selection - White, Halbert; Lu, Xun (The Review of Economics and Statistics, 2011)
Careful examination of the structure determining treatment choice and outcomes, as advocated by Heckman (2008), is central to the design of treatment effect estimators and, in particular, proper choice of covariates. Here, we demonstrate how causal diagrams developed in the machine learning literature by Judea Pearl and his colleagues, but not so well known to economists, can play a key role in this examination by using these methods to give a detailed analysis of the choice of efficient covariates identified by Hahn (2004).